2020
DOI: 10.3390/ijerph17124423
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Physical Activity Levels and Mental Health in Individuals with Spinal Cord Injury in South Korea

Abstract: Background: The aim of this study was to assess the relationship between physical activity (PA) levels and mental health in individuals with spinal cord injury (SCI). Methods: Three hospitals in the Seoul metropolitan area were invited to recruit patients with SCI (n = 103). PA levels were measured by the Leisure Score Index of the Godin Leisure-Time Exercise Questionnaire (GLTEQ). The Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder-7 (GAD-7) questionnaire, and Multidimensional Scale o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The Patient Health Questionnaire‐9 (PHQ‐9) and the General Anxiety Disorder‐7 (GAD‐7) scale were two of the validated tools used 22,23 . The PHQ‐9 has been found to be a highly sensitive (100%) and specific (84%) screening tool for depression that is used extensively among individuals with SCI 18,24,25 . GAD‐7 has also been used in this population, but to a lesser extent 18 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Patient Health Questionnaire‐9 (PHQ‐9) and the General Anxiety Disorder‐7 (GAD‐7) scale were two of the validated tools used 22,23 . The PHQ‐9 has been found to be a highly sensitive (100%) and specific (84%) screening tool for depression that is used extensively among individuals with SCI 18,24,25 . GAD‐7 has also been used in this population, but to a lesser extent 18 .…”
Section: Methodsmentioning
confidence: 99%
“…16,17 Furthermore, self-isolation introduced to prevent the spread of infection may have additional unintended negative effects, such as limiting access to in-person care aides and negatively affecting the physical and mental health of individuals with SCI. 18 In a meta-analysis of 19 studies spanning 35,676 pa, Williams and Murray 11 estimated the mean prevalence of depression among individuals with SCI to be 22.2%, with a lower-bound estimate of 18.7% to an upper-bound estimate of 26.3%. 11 To this end, fear and anxiety of contracting COVID-19 and perceived vulnerability may be further contributors to worsening mental health.…”
Section: Introductionmentioning
confidence: 99%
“…For adults with spinal cord injury (SCI), aerobic exercise is beneficial for improving indices of physical [ 1 ] and mental [ 2 ] health. On this theme, scientific guidelines published in 2018 describe the dose of aerobic exercise required to improve cardiorespiratory fitness and cardiometabolic health in adults with SCI [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study participation in moderate PA was higher as compared to mild and heavy PA. Whereas a study was done in South Korea reported that mild PA performed by the SCI patients were higher than moderate and heavy PA Although the reports from this study also shows that slight depression was associated with PA but it did not associate depression with different intensity levels of PA [24]. A study was done by Ganesh et al on paraplegia patients to find out about the PA levels in Odisha, India.…”
Section: Discussionmentioning
confidence: 57%